Serum Progranulin Levels and Disease Activity in Patients with Axial Spondyloarthritis - Mercan, Irem; Oktayoglu, Pelin; Mete, Nuriye; Caglayan, Mehmet (Aktuelle Rheumatologie, 2023)
Background Axial spondyloarthritides (ax-SpA) are a group of chronic systemic diseases of unknown aetiology, affecting mostly young men, with common features such as inflammatory low back pain, axial skeletal involvement, sacroiliitis, and association with HLA-B27. Inflammatory cytokines, mainly TNF-α, play a role in its aetiopathogenesis. Progranulin (PGRN) is thought to be an anti-inflammatory molecule that acts through the TNF-α pathway. In our study, we aimed to investigate the relationship between serum PGRN levels and disease activity in patients with AS.Material and Methods Forty-five patients between the ages of 18 and 65 who were classified as having ax-SpA according to ASAS classification criteria were included in our study. Forty-five individuals between the ages of 18 and 65 who did not have pregnancy or lactation status, no acute or chronic infection and no malignancy or rheumatic disease were included as the healthy control group. In addition, BASDAI, BASFI, BASMI, ASDAS-CRP, ESR and CRP levels were recorded in the patient group to determine the laboratory and clinical findings of patients with ax-SpA.Results Mean serum progranulin levels were higher in axial SpA patients compared with the control group (5156.72±1274.34 vs. 4836.50±1422.10), but this result was not statistically significant (p=0.275). Serum progranulin levels were negatively correlated with ESR (p=0.031) but ASDAS-CRP (p=0.407) and BASDAI (p=0.297) values were not correlated with the progranulin levels.Conclusion Although we found a negative correlation between progranulin and ESR, we did not find any association between progranulin and disease activity in patients with axSpA. There is a need for new and larger studies to be conducted with a higher number of participants in this patient group and to measure serum PGRN levels as well as antibodies against PGRN.
Keywords: axialspondyloarthritis; progranulin; disease activity